Draft Annual Plan 1994-95 Volume-III Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1994)
As per 1991 Census there were about 46000 children of the age group 0-6 in this Union Territory. Out of this about 15000 children may come in the age group of 3-5 every year in feeder and support programme category of Primary Education. Presently we are having Pre-Primary Classes in 68 schools in this territory both Govt, and Private and 255 Anganwadis run by ICDS to cater to the needs of those children which is inadequate.
Andaman and Nicobar Administration